Public policies, gender, and STEM careers - Casagrande, Ana Lara (2023)
In this work, the role of the State in public policies that subsidize the guarantee of social rights is discussed, as well as gender disparities are addressed as a historical product of the discrimination to which women have been subjected and which result in their absence in STEM careers. (Science, Technology, Engineering and Mathematics). The mapping of existing public policies and the requirement that advances be established is a necessity to allow equal access for women to opportunities and spaces of power.